The combined effect of three floating macrophytes in domestic wastewater treatment - AKOWANOU, Akuemaho Virgile Onésime; DEGUENON, Hontonho Espérance Justine; Balogoun, Kolawolé Clément; Daouda, Mohamed Moukorab Arêmou; AÏNA, MARTIN PÉPIN (My University, 2023)
We conducted this study to assess the efficiency of the combination of three floating macrophytes (Eichhornia crassipes (water hyacinth), Pistia stratiotes L. (water lettuce), and Lemna minor L. (duckweed)) for the treatment of domestic wastewater. The experiments were performed on a pilot scale consisting of four basins aligned in series: one anaerobic pond, two facultative ponds (containing water hyacinth and water lettuce respectively), and one maturation pond (containing duckweed). The study showed that combining the different macrophytes studied led to significantly reduced pollution in domestic wastewa- ter. Based on inlet pollution loads, water hyacinth pond better eliminate carbon pollution. The water lettuce pond was good at removing nitrogen pollution, and the duckweed pond better-eliminated phosphorus. The overall yield for TSS, COD, BOD5, TKN, and PO43− was 92%, 98%, 98%, 87%, and 80% respectively. Based on the results, combining different floating macrophytes in a domestic wastewater treatment plant could improve its overall treatment performance.
Keywords: Domestic wastewater Purification efficiency Macrophytes